IMPLEMENTASI AKUNTANSI SYARIAH DALAM BISNIS: TANTANGAN DAN MANFAAT - Muhammad Mustaghfirin; Eny Latifah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
The purpose of this study is to examine the benefits and challenges of implementing Islamic accounting in business. The research method used is descriptive qualitative with the type of literature. The results of the study are the challenges of sharia accounting in business include changes in mentality, limited human resources competent in sharia, development of consistent sharia accounting standards, supporting technological infrastructure, and difficulties in leaving the conventional accounting paradigm. A focus on developing human resource competencies, improving Islamic accounting standards, and utilising appropriate technology will be key in facing and overcoming the challenges of effectively applying Islamic accounting in business. Islamic accounting has benefits: strengthening business accountability and transparency, enhancing customer confidence through sharia principles, and improving the efficiency and effectiveness of financial management. In addition, Islamic accounting promotes compliance with ethical principles and strengthens business competitiveness. Overall, Islamic accounting acts as an important pillar in conducting business in accordance with Islamic sharia principles, which in turn can strengthen the integrity and sustainability of the business.